The relationships between care burden and sleep quality in migrant care workers: an evaluation of the mediating factors - I-Ming Chen; Jia-Chi Shan; Tzu-Yun Lin; Jennifer Yi-Ying Chen; Po-Chang Tseng; Yu-Hsuan Lin; Shih-Cheng Liao; Hsi-Chung Chen (Critical Public Health)
Care burden can compromise the sleep quality of migrant care workers (MCW); however, factors that influence this adverse effect remain unknown. This study aims to examine the psychological and behavioral factors that mediate the relationship between care burden and poor sleep quality in MCW in Taiwan. MCW in Taiwan were recruited and interviewed using online computer-assisted data collection system. Care burden was measured based on the total number of psychiatric symptoms in care recipients. Psychological and behavioral factors were evaluated using the Patient Health Questionnaire for depression and the Sleep Hygiene Index for sleep hygiene. Subjective sleep quality was measured using the Pittsburgh Sleep Quality Index. A multiple mediation model was used to estimate the direct effect of care burden and indirect effect of psychological and behavioral mediators on poor sleep quality. The multiple mediation models controlled for various covariates revealed that care burden did not lead to poor sleep quality directly, however, it compromised sleep quality indirectly by contributing to depression and poor sleep hygiene, respectively. The results of this study show that MCW’s care burdens indirectly affect sleep quality through depression and sleep hygiene. Intervention strategies should target depression and sleep hygiene to mitigate the adverse impact of care burdens on sleep quality.